Pembuatan Aplikasi Perpustakaan Digital Untuk Anak-Anak Kampung Stamplat, Desa Indragiri, Kabupaten Bandung - Jimmy Agustian Loekito; Hendry Wong; Deni Setiawan; Yosafat Pranata (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2022)
Indragiri Village is located in Rancabali District, Bandung Regency, has four dusun spread out, one of which is Dusun Ciparay which contains Kampung Stamplat. In this village live 28 heads of families who generally make a living as vegetable farmers, coffee farmers, ranchers, and tea plantation employees. The role of information technology includes library management information systems, both in conventional libraries (electronic book catalogues) and digital libraries which are oriented to digital data and komputer networks. Book collections in the library are also transferred to electronic media, for example collections of journals, proceedings, and textbooks in the form of e-books. The purpose of community service activities (PkM) in this paper is the purpose of the first phase of activity, namely making digital library applications (software) for children in Kampung Stamplat, Dusun Ciparay, Indragiri Village, Rancabali District, Bandung Regency. The scope of PkM activities in the first stage is the results of application products installed on komputers, making training modules for using applications. The purpose of the second phase of activity (continued) is the socialization and training on the use of applications for the children of Kampung Stamplat which will be realized in September s.d. October 2021 through 3 training activities. The results of the activities that can be conveyed in this scientific paper are digital library application products that will be used by the children of Kampung Stamplat, Dusun Ciparay, Indragiri Village, Rancabali District, Bandung Regency as a digital learning medium. The digital library can be accessed by all children in Kampung Stamplat as a learning companion media, especially studying materials related to the curriculum for both elementary and junior high schools.